Occurrence of Thromboembolism in Paediatric Patients With Inflammatory Bowel Disease: Data From the CEDATA-GPGE Registry - Jan De Laffolie; Antje Ballauff; Stefan Wirth; Carolin Blueml; Frank Risto Rommel; Martin Claßen; Martin Laaß; Thomas Lang; Almuthe Christina Hauer; the CEDATA-GPGE Study Group (Frontiers Media S.A., 2022)
ObjectiveAmong patients with inflammatory bowel disease (IBD), the risk of thromboembolism (TE) is increased, representing a relevant cause of morbidity and mortality. In contrast to other extraintestinal IBD manifestations, TE receives much less attention because of its low incidence, estimated at merely 0.4-0.9% in hospitalised children with IBD.MethodsCases with TE, as documented in the German-Austrian Paediatric IBD registry gesellschaft für pädiatrische gastroenterologie und ernährung - large paediatric patient registry (CEDATA-GPGE), were analyzed retrospectively. For all patients with signs of TE, a questionnaire was filled in by the treating paediatric gastroenterologist.ResultsOver 10 years, 4,153 paediatric patients with IBD (0-18 years) were registered in the registry, and 12 of them identified with TE. Eight patients were diagnosed with ulcerative colitis (UC), three with Crohn's disease (CD), and one with IBD-unclassified. The median age at IBD diagnosis was 10 years and at the manifestation of TE 13 years, respectively, with a median latency to TE of 2 years. Prevalence of TE was 0.3%, with a significantly higher risk for patients with UC than CD (OR 5.9, CI 1.56-22.33, p = 0.008). More girls than boys were affected (f:m = 7:5) without reaching significance. Approximately 90% of patients experienced TE during active disease, with relevant cerebral and limb involvement in 6/12 patients. Various risk factors, e.g., hospitalisation, coagulopathy, or anaemia were identified. TE management included intensive care and surgery. Among the 12 patients, 11 recovered fully, in which one patient has focal epilepsy as a sequela.ConclusionPaediatric patients with IBD have a substantially increased risk for TE. Risk factors, such as those identified should be considered when managing paediatric IBD and preventive measures for those hospitalised taken routinely. Initiating pharmacological thromboprophylaxis is challenging for the lack of published trials on efficacy and safety in paediatric IBD but should be considered carefully in each case.